Comprehensive lipidomics analysis of the lipids in hazelnut oil during storage. (1st June 2022) - Sun, Jiayang; Hu, Pengpeng; Lyu, Chunmao; Tian, Jinlong; Meng, Xianjun; Tan, Hui; Dong, Wenxuan
Highlights: We dynamically monitored the alteration of lipid composition in hazelnut oil during storage by UPLC-QTOF-MS. Ten subclasses of 103 lipids were identified in hazelnut oil. Fifty one lipids were significantly different between fresh and oxidized hazelnut oil. Glycerophospholipid metabolism is the most important lipid metabolic pathway during hazelnut oil storage. Our results provided insight into alterations in hazelnut lipids during storage. Abstract: Although hazelnut oil is is nutritious, it is easily oxidized during storage. Thus far, changes in lipids during storage have not been comprehensively analyzed. Here, we used ultra-high liquid chromatography tandem quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) to dynamically monitor the lipid composition of hazelnut oil during accelerated storage for 24 d. A total of 10 subclasses of 103 lipids were identified. After 24 d, the content of triacylglycerol, diacylglycerol, phosphatidic acid, phosphatidylethanolamine, phosphatidylethanol, ceramide, and total lipids decreased significantly (P < 0.05). A total of 51 significantly different lipids were screened (Variable Importance in Projection > 1, P < 0.05), and these lipids could be used as biomarkers to distinguish fresh and oxidized hazelnut oil. We also detected seven most important pathways by bioinformatics analysis to explore the mechanism underlying changes. Our results provide useful information for future applications of hazelnut oil and provide new insight into edible oil oxidation.